Neobavaisoflavone Induces Bilirubin Metabolizing Enzyme UGT1A1 via PPARα and PPARγ - Zhu, Ya-Di; Guan, Xiao-Qing; Chen, Jing; Peng, Sheng; Finel, Moshe; Zhao, Ying-Yuan; Wang, Rui-Min; Bi, Hui-Chang; Lei, Ming; Wang, Dan-Dan; Ge, Guang-Bo (Frontiers in Pharmacology, 2021)
UDP-glucuronosyltransferase 1A1 (UGT1A1) is an essential enzyme in mammals that is responsible for detoxification and metabolic clearance of the endogenous toxin bilirubin and a variety of xenobiotics, including some crucial therapeutic drugs. Discovery of potent and safe UGT1A1 inducers will provide an alternative therapy for ameliorating hyperbilirubinaemia and drug-induced hepatoxicity. This study aims to find efficacious UGT1A1 inducer(s) from natural flavonoids, and to reveal the mechanism involved in up-regulating of this key conjugative enzyme by the flavonoid(s) with strong UGT1A1 induction activity. Among all the tested flavonoids, neobavaisoflavone (NBIF) displayed the most potent UGT1A1 induction activity, while its inductive effects were confirmed by both western blot and glucuronidation activity assays. The nuclear receptor reporter assays demonstrated that NBIF activated PPARα and PPARγ in a dose-dependent manner. Meanwhile, we also found that NBIF could up-regulate the expression of PPARα and PPARγ, suggesting that the induction of UGT1A1 by NBIF was mainly mediated by PPARs. In silico simulations showed that NBIF could stably bind on pocket II of PPARα and PPARγ. These findings suggested that NBIF can be used as a promising lead compound for the development of more efficacious UGT1A1 inducers to treat hyperbilirubinaemia and UGT1A1-associated drug toxicities.